2018
DOI: 10.1016/j.ijthermalsci.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of pool boiling on smooth, vertically aligned tandem tubes

Abstract: Research highlights  3D numerical simulation of nucleate pool boiling in atmospheric pressure  Superior heat transfer capacity of water in contrast with ethanol and FC-72  Heat transfer coefficient decreases with increase of the tube inclination angle  Optimum inclination angle is found to be 30° for the specified operating conditions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…The results of the pool-boiling curve and pool boiling heat transfer coefficient PBHTC of water for a range of heat fluxes 29 -87 ( / 2 ) are presented in Figure 3 and 4. The present simulation results were validated with the experimental work of [29] and numerical work of [1], and the results of pool boiling curve and heat transfer coefficient are in good agreement with this experimental study, and this is because we used same geometry and boundary condition of [29]. The total heat flux was found to be close to experimental heat flux after taking in our consideration the uncertainties of the mentioned experimental work.…”
Section: Model Validationsupporting
confidence: 80%
See 2 more Smart Citations
“…The results of the pool-boiling curve and pool boiling heat transfer coefficient PBHTC of water for a range of heat fluxes 29 -87 ( / 2 ) are presented in Figure 3 and 4. The present simulation results were validated with the experimental work of [29] and numerical work of [1], and the results of pool boiling curve and heat transfer coefficient are in good agreement with this experimental study, and this is because we used same geometry and boundary condition of [29]. The total heat flux was found to be close to experimental heat flux after taking in our consideration the uncertainties of the mentioned experimental work.…”
Section: Model Validationsupporting
confidence: 80%
“…Two sets of conservation equations which govern the balance of mass, momentum, and energy of each phase are presented as follows [1,17]:…”
Section: Mathematical Formulation 21 Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9], where it was suggested that significant flow of heat is caused by the gradual, albeit quick, rewetting of the 'dry' portion of solid surface beneath a departing bubble. A better understanding of these processes is crucial for the development of computational models of boiling flows, and in particular of macroscopic two-fluid CFD techniques, which require closure relations for sub-grid scale models of wall-boiling heat transfer, and are used in a broad range of pool [10] and forced flow [11] [12] boiling calculations.…”
Section: Introductionmentioning
confidence: 99%